Pengaruh Model Pembelajaran Problem Based Learning (PBL) Terhadap Kemampuan Berpikir Kritis dan Respon Siswa Kelas VIII MTs. Putri Al-Ishlahuddiny Kediri Lombok Barat - Lalu Muktar; Rokyal Aini; Mohan Taufiq Mashuri; Aulia Zulfaeda; Bq Siti Maulida Azmi (Otus Edu Journal Prodi Tadris IPA Biologi UIN Mataram, 2023)
This research aims to determine whether there is an influence of the Problem Based Learning (PBL) learning model on the critical thinking abilities of class VIII MTs students. Putri Al-Ishlahuddiny Kediri, West Lombok. This research is a quasi-experiment research with a quantitative approach, non-equivalent control group research design. The population in this study were all class VIII students consisting of 4 (four) classes. The sampling technique uses cluster random sampling technique. The sample in this study was 42 students from class VIII C as the control class and 41 students from class VIII D as the experimental class. The research instrument uses tests. Based on the research results, the average pretest score for the control class was 24.31 and the average pretest score for the experimental class was 24.29, while the average score for the experimental class posttest was higher than the control class posttest with the average posttest class score the experimental score was 68.29 and the average posttest score for the control class was 62.92 and was included in the equally high class category. Apart from that, the average N-Gain value for the experimental class is 0.57 and the average N-Gain value for the control class is 0.50. The difference in increase from pretest to posttest for the experimental class was 44, while for the control class it was 28.61. Further test results based on the t test using paired samples test show a significant value of 0.000 < 0.05, so it can be seen that H0 is rejected and H1 is accepted.